2011
DOI: 10.1136/ard.2011.155382
|View full text |Cite
|
Sign up to set email alerts
|

IgG4 immune response in Churg–Strauss syndrome

Abstract: ObjectiveT-helper type 2 responses are crucial in Churg–Strauss syndrome (CSS) and may enhance the production of IgG4 antibodies. The authors assessed the IgG4 immune response in CSS patients.MethodsThe authors included 46 consecutive patients with CSS (24 with active and 22 with quiescent disease), 26 with granulomatosis with polyangiitis (GPA, Wegener's), 25 with atopic asthma and 20 healthy controls and determined serum IgG, IgM, IgA, IgE and IgG subclass levels. Tissue infiltration by IgG4 plasma cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(105 citation statements)
references
References 21 publications
5
92
0
8
Order By: Relevance
“…We considered EGPA because of the history of asthma, mononeuropathy multiplex, eosinophilia and leukocytoclastic vasculitis. Additionally, high levels of serum IgG4 have been reported with EGPA (26). However, a negative result for ANCA and a lack of literature on concomitant cryoglobulinemia eliminated a diagnosis of EGPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered EGPA because of the history of asthma, mononeuropathy multiplex, eosinophilia and leukocytoclastic vasculitis. Additionally, high levels of serum IgG4 have been reported with EGPA (26). However, a negative result for ANCA and a lack of literature on concomitant cryoglobulinemia eliminated a diagnosis of EGPA.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilia is a common feature of IgG4-RD (3) and an association between IgG4-RD and conditions like allergic rhinitis or asthma has been reported (12). In EGPA, an increase in IgG4-positive plasma cells is not as prominent (not more than 40% of the infiltrating IgG-positive plasma cells) (26), as it is in IgG4-RD.…”
Section: Discussionmentioning
confidence: 99%
“…Serum total IgE levels are elevated in most patients but they lack specificity for common allergens [45]. Recent data have shown that serum IgG4 levels were high in 75% of patients with active EGPA, better correlating with its activity than IgE [62]. ANCA may appear several years before the onset of vasculitis [63].…”
Section: Blood Cells and Biomarkersmentioning
confidence: 99%
“…Salivary gland biopsy demonstrated vasculitis in one case and eosinophilic granulomas in the remaining two cases (27Á29). In some of these patients, elevated serum IgG4 levels and infiltration of IgG4-positive plasmacytes in the nasal mucosa were observed, which suggests some common pathogenic mechanisms between IgG4-related disease and EGPA (31,32).…”
mentioning
confidence: 97%